Climate, host and geography shape insect and fungal communities of trees - Franić, Iva (2023)
Funding Information: We gratefully acknowledge the financial support of the Swiss National Science Foundation (Project C15.0081) Grant 174644 and the Swiss Federal Office for the Environment Grant 00.0418.PZ/P193-1077. This work was supported by COST Action “Global Warning” (FP1401). CABI is an international intergovernmental organisation, and R.E., M.K., H.L. and I.F. gratefully acknowledge the core financial support from our member countries (and lead agencies) including the United Kingdom (Foreign, Commonwealth and Development Office), China (Chinese Ministry of Agriculture and Rural Affairs), Australia (Australian Centre for International Agricultural Research), Canada (Agriculture and Agri-Food Canada), Netherlands (Directorate General for International Cooperation), and Switzerland (Swiss Agency for Development and Cooperation). See https://www.cabi.org/aboutcabi/who-we-work-with/key-donors/ for full details. M.B. and M.K.H. were financially supported by the Slovak Research and Development Agency (Project APVV-19-0116). H.B. would like to thank the botanist Jorge Capelo who helped with Myrtaceae identification and INIAV IP for supporting her contribution to this study. Contributions of M. de G. and B.P. were financed through Slovenian Research Agency (P4-0107) and by the Slovenian Ministry of Agriculture, Forestry and Food (Public Forestry Service). G.C, C.B.E. and A.F.M. were supported by OTKA 128008 research grant provided by the National Research, Development and Innovation Office. Contributions of K.A. and R.D. were supported by the Estonian Research Council grants PSG136 and PRG1615. M.J.J., C.L.M. and H.P.R. were financially supported by the 15. Juni Fonden (Grant 2017-N-123). P.B., B.G. and M.Ka. were financially supported by the Ministry of Science and Higher Education of the Republic of Poland for the University of Agriculture in Krakow (SUB/040013-D019). C.N. was financially supported by the Slovak Research and Development Agency (Grant APVV-15-0531). N.K. was partially supported by the Russian Science Foundation (grant № 22-16-00075) [species identification] and the basic project of Sukachev Institute of Forest SB RAS (№ FWES-2021-0011) [data analysis]. R.OH. was supported by funding from DAERA, and assistance from David Craig, AFBI. T.P. thanks the South African Department of Forestry, Fisheries and the Environment (DFFE) for funding noting that this publication does not necessarily represent the views or opinions of DFFE or its employees. In preparing the publication, materials of the bioresource scientific collection of the CSBG SB RAS “Collections of living plants indoors and outdoors” USU_440534 (Novosibirsk, Russia) were used. M.Z. was financially supported by Ministry of Science, Technological Development and Innovation of the Republic of Serbia (contract no. 451-03-47/2023-01/200197). We acknowledge the Genetic Diversity Centre (GDC) at ETH Zurich for providing computational infrastructure and acknowledge the contribution of McGill University and Génome Québec Innovation Center (Montréal, Quebec, Canada) for pair-end sequencing on Illumina MiSeq. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. Funding Information: We gratefully acknowledge the financial support of the Swiss National Science Foundation (Project C15.0081) Grant 174644 and the Swiss Federal Office for the Environment Grant 00.0418.PZ/P193-1077. This work was supported by COST Action “Global Warning” (FP1401). CABI is an international intergovernmental organisation, and R.E., M.K., H.L. and I.F. gratefully acknowledge the core financial support from our member countries (and lead agencies) including the United Kingdom (Foreign, Commonwealth and Development Office), China (Chinese Ministry of Agriculture and Rural Affairs), Australia (Australian Centre for International Agricultural Research), Canada (Agriculture and Agri-Food Canada), Netherlands (Directorate General for International Cooperation), and Switzerland (Swiss Agency for Development and Cooperation). See https://www.cabi.org/aboutcabi/who-we-work-with/key-donors/ for full details. M.B. and M.K.H. were financially supported by the Slovak Research and Development Agency (Project APVV-19-0116). H.B. would like to thank the botanist Jorge Capelo who helped with Myrtaceae identification and INIAV IP for supporting her contribution to this study. Contributions of M. de G. and B.P. were financed through Slovenian Research Agency (P4-0107) and by the Slovenian Ministry of Agriculture, Forestry and Food (Public Forestry Service). G.C, C.B.E. and A.F.M. were supported by OTKA 128008 research grant provided by the National Research, Development and Innovation Office. Contributions of K.A. and R.D. were supported by the Estonian Research Council grants PSG136 and PRG1615. M.J.J., C.L.M. and H.P.R. were financially supported by the 15. Juni Fonden (Grant 2017-N-123). P.B., B.G. and M.Ka. were financially supported by the Ministry of Science and Higher Education of the Republic of Poland for the University of Agriculture in Krakow (SUB/040013-D019). C.N. was financially supported by the Slovak Research and Development Agency (Grant APVV-15-0531). N.K. was partially supported by the Russian Science Foundation (grant № 22-16-00075) [species identification] and the basic project of Sukachev Institute of Forest SB RAS (№ FWES-2021-0011) [data analysis]. R.OH. was supported by funding from DAERA, and assistance from David Craig, AFBI. T.P. thanks the South African Department of Forestry, Fisheries and the Environment (DFFE) for funding noting that this publication does not necessarily represent the views or opinions of DFFE or its employees. In preparing the publication, materials of the bioresource scientific collection of the CSBG SB RAS “Collections of living plants indoors and outdoors” USU_440534 (Novosibirsk, Russia) were used. M.Z. was financially supported by Ministry of Science, Technological Development and Innovation of the Republic of Serbia (contract no. 451-03-47/2023-01/200197). We acknowledge the Genetic Diversity Centre (GDC) at ETH Zurich for providing computational infrastructure and acknowledge the contribution of McGill University and Génome Québec Innovation Center (Montréal, Quebec, Canada) for pair-end sequencing on Illumina MiSeq. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. Publisher Copyright: © 2023, The Author(s).